Tacit Collusion under Destination- and Origin-Based Commodity Taxation - Andreas Haufler; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2000)
The paper employs a standard model of dynamic price competition to study how international principles of value-added taxation affect the stability of collusive agreements when producers in an international duopoly agree not to export into each other's home market and tax rates differ across countries. In this framework, tacit collusion may be more likely to break up under either the destination or the origin principle, depending on the relation between costs of production and market size. A robust result is that tax rate harmonization increases the likelihood of tacit collusion under both tax principles considered.
Keywords: 330; Commodity taxation; dynamic price competition